Saving the world : a brief history of communication for development and social change - McAnany, Emile G. (History of communication., 2012)
Drawing on the pioneering works of Daniel Lerner, Everett Rogers, and Wilbur Schramm as well as his own personal experiences in the field, McAnany builds a new, historically cognizant paradigm of communication for development and social change for the future that supplements technology with social entrepreneurship.